Supply Chain Management and Advanced Planning Concepts, Models, Software, and Case Studies - Stadtler, Hartmut; Kilger, Christoph (Springer Berlin Heidelberg : Imprint: Springer, 2008)
Supply Chain Management, Enterprise Resources Planning (ERP), and Advanced Planning Systems (APS) are important concepts in order to organize and optimize the flow of goods, materials, information and funds. This book, already in its fourth edition, gives a broad and up-to-date overview of the concepts underlying APS. Special emphasis is given to modeling supply chains and implementing APS successfully in industry. Understanding is enhanced by several case studies covering a wide range of industrial sectors. The fourth edition contains updated material, rewritten chapters and additional case studies.